2017
DOI: 10.1002/ajh.24906
|View full text |Cite
|
Sign up to set email alerts
|

A clinically meaningful fetal hemoglobin threshold for children with sickle cell anemia during hydroxyurea therapy

Abstract: Hydroxyurea has proven clinical benefits and is recommended to be offered to all children with sickle cell anemia (SCA), but the optimal dosing regimen remains controversial. Induction of red blood cell fetal hemoglobin (HbF) by hydroxyurea appears to be dose-dependent. However, it is unknown whether maximizing HbF% improves clinical outcomes. HUSTLE (NCT00305175) is a prospective observational study with a primary goal of describing the long-term clinical effects of hydroxyurea escalated to maximal tolerated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(74 citation statements)
references
References 45 publications
(51 reference statements)
3
68
1
Order By: Relevance
“…Estepp et al recently reported that an HbF threshold of 20% may serve as a useful target for therapy . This was not a target for dose titration in our cohort and the HbF levels achieved were relatively low at 12.9 ± 0.9%, with only 15 patients (16.1%) demonstrating responses in HbF reaching >20%.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…Estepp et al recently reported that an HbF threshold of 20% may serve as a useful target for therapy . This was not a target for dose titration in our cohort and the HbF levels achieved were relatively low at 12.9 ± 0.9%, with only 15 patients (16.1%) demonstrating responses in HbF reaching >20%.…”
Section: Discussionsupporting
confidence: 45%
“…This was not a target for dose titration in our cohort and the HbF levels achieved were relatively low at 12.9 ± 0.9%, with only 15 patients (16.1%) demonstrating responses in HbF reaching >20%. Despite this, the clinical outcomes of our study (0.56 hospitalisations/year) were comparable to that of the Hydroxyurea Study of Long‐Term Effects (HUSTLE) study, which was reported to be 0.5 hospitalisations/year in the HbF >20% group, and others that have operated under the MTD protocol . In conjunction with the fact that patients who were maintained on ANC <4 × 10 9 /L did not achieve better clinical outcomes, these findings suggest that the MTD regime may not necessarily translate into superior clinical benefit.…”
Section: Discussionsupporting
confidence: 45%
“…Hydroxyurea is FDA approved in pediatrics and adults to reduce the frequency of these vaso‐occlusive pain events and prevent hospitalizations; however, many adult patients with frequent sickle cell pain‐related events are not receiving hydroxyurea . Among those prescribed hydroxyurea, aggressive titration to maximal tolerated dose and strict adherence may provide additional benefits for pain outcomes . However, limited data exist that examine outcomes for hydroxyurea in patients who progress to recurrent vaso‐occlusive pain crisis or chronic pain.…”
Section: Introductionmentioning
confidence: 99%
“…The sickle cell team and the entire clinic staff are consistent in encouraging and conscientiously enforcing HU compliance. Our goal is to achieve as high a HgbF level as possible, since maximizing HgbF percent improves clinical outcomes . We believe maintaining HgbF in the 30% range was a major reason for the lack of sickle cell complications in this cohort.…”
Section: Discussionmentioning
confidence: 91%